A novel SVPWM for 3-phase to 5-phase conversion using matrix converter - Palanisamy Ramasamy; Kalyanasundaram Vakesan; Vijayakumar Govindaraj; Shanmugasundaram Venkatarajan; Saumitra Chattopadhyay; Vidyasagar Sugavanam (Institute of Advanced Engineering and Science, 2022)
A novel matrix converter has been developed for 3-phase to 5-phase conversion using a novel space vector pulse width modulation. The matrix converter organized to generate 5-phase AC output voltage from 3-phase input voltage with help of SVPWM method; bidirectional power switches placed in matrix converter controlled by appropriate switching pulse. Space vector pulse width modulation (SVPWM) provides better utilization of applied input voltage, improved output voltage, reduced total harmonic distortion. The bidirectional switch used by the matrix converter decreases stress on the power switch and the influence of harmonic fluctuation in AC output voltage. When compared to traditional approaches, the suggested system offers improved output voltage and current control. Using MATLAB/Simulink and FPGA-cyclone controller, respectively, modelling and experimental results have been given to validate the proposed methodology.